2015
DOI: 10.2298/tsci140107100k
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of developing turbulent flow and heat transfer in ribbed convergent/divergent rectangular ducts

Abstract: The article represents an experimental investigation of friction and heat transfer characteristics of divergent / convergent rectangular ducts with an inclination angle of 1? in the y-axis. Measurements were taken for a convergent / divergent rectangular duct of aspect ratio AR at inlet1.25 and outlet in convergent channel 1.35; but in case of divergent duct it can be reversed. The four uniform rib heights, e = 3, 6, 9 and 12 mm the ratio between rib height to hydraulic mean diameter (e/Dm) are 34.8, 69.7, 104… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Bhadouriya et al (2015) conducted experimental and numerical study of fluid flow and heat transfer in a twisted square duct. Karthikeyan et al (2015) presented experimental study of developing turbulent flow and heat transfer in ribbed convergent and divergent rectangular ducts. Zhang et al (2021) studied flow characteristics and structural parametric optimization design of rectangular plenum chambers for HVAC systems.…”
Section: Introductionmentioning
confidence: 99%
“…Bhadouriya et al (2015) conducted experimental and numerical study of fluid flow and heat transfer in a twisted square duct. Karthikeyan et al (2015) presented experimental study of developing turbulent flow and heat transfer in ribbed convergent and divergent rectangular ducts. Zhang et al (2021) studied flow characteristics and structural parametric optimization design of rectangular plenum chambers for HVAC systems.…”
Section: Introductionmentioning
confidence: 99%
“…The MHD flow and heat transfer in the presence of a confined square cylinder was investigated by Farahi and Hossein [20], using the SM82 equations. Karthikeyan et al [21] presented the experimental study of developing turbulent flow and heat transfer in ribbed convergent /divergent rectangular ducts. Fully developed laminar flow and heat transfer in a 2-D horizontal channel with staggered fins was numerically analyzed by Turgut and Arslan [22].…”
Section: Introductionmentioning
confidence: 99%
“…Heat transfer characteristics of a wavy walled duct have been analyzed numerically by Ramgadia et al [2]. Karthikeyan et al [3] carried out an experimental investigation on developing turbulent flow and heat transfer in a convergent-divergent rectangular ribbed duct with an inclination angle of 1 0 to the y-axis using four different rib heights similar to the work of Wang et al [4] and it has been reported that that the divergent duct gives better result in heat transfer enhancement for all rib heights. Promvonge et al [5] found that the rise of blockage ratio leads to enhancement in heat transfer and friction losses in a square duct with inline 60 0 V-shaped ribs mounted on two opposite walls.…”
Section: Introductionmentioning
confidence: 99%